The clinically extremely vulnerable to COVID: Identification and changes in healthcare while self-isolating (shielding) during the coronavirus pandemic. (2022) - Butler, Jessica; Nath, Mintu; Blana, Dimitra; Ball, William; Beech, Nicola; Black, Corri; Osler, Graham; Peytrignet, Sebastien
No abstract available